World religions (Macmillan compendium, 1997)
World Religions extracts the essential articles from the Dartmouth Medal-winning, Encyclopedia of Religion, providing a concise version of one of the most honored reference works of all time. The Compendium is a handy desk reference, and an affordable and space-saving alternative for libraries not in need of the exhaustive coverage afforded by the parent set. The selection of articles reflects the global and multidisciplinary nature of the comprehensive edition, and includes a full index and bibliographies.